Pension fund flows, exchange rates, and covered interest rate parity - Aldunate, Felipe; Da, Zhi; Larrain, Borja; Sialm, Clemens (Journal of Financial Economics, 2025)
Frequent, yet uninformed, market timing recommendations by a financial advisory firm generate significant flows for Chilean pension funds. These flows induce substantial changes in the Chilean foreign exchange rate due to the funds’ high allocation to international securities. Local banks provide liquidity to pension funds in the spot market and their hedging transactions propagate the demand fluctuations from the spot to the forward market, resulting in deviations from covered interest rate parity. Using bank balance sheet data, we confirm that banks’ risk bearing constraints create limits to arbitrage.